E-Commerce and ethical web design applying the BBBonline guidelines on Malaysian website - Hussin, Husnayati; Suhaimi, Mohd Adam; Mustafa, Maram (Zarqa University, Jordan, 2005)
The aim of this study is to find out to what extent Malaysian companies incorporate trustworthy elements on their websites. The study provides a detail website evaluation based on the principles for ethical online business provided by the BBBOnline guidelines. The five principles used as an evaluation instrument are: (1) Truthful and accurate communication, (2) Disclosure, (3) Information practices and security, (4) Customer satisfaction, and (5) Protecting children. The study selected ten Malaysian-based companies which adopt e-commerce as part of their business. The finding of the study indicate that some principles are well-adhered to, while others need more attention.